The Impact of Online Learning on Digital Literacy Skills in Higher Education: Survey Methods and Test Analysis - Kurniaman, Otang; Hadriana; Islami, Nur; Hainul Putra, Zetra; Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Covid-19 Pandemic had impacts on the learning system in Indonesia, especially in Pekanbaru. It changes the system into online learning. Consequently, the Indonesian government should provide facilitation of the internet and other services in order to achieve successful learning. Hence, this paper provides a description of the influence that appeared from the learning system implemented on University students’ digital literacy. Digital literacy is someone’s ability to comprehend information as a learning source. The research uses a survey method in the form of a questionnaire and tests through SPSS. The result indicates that based on the two top universities in Pekanbaru by using stratified random sampling, there is no influence of online learning implementation for the two classes. Meanwhile, there is an influence for the four classes, which consisted of two classes that indicate positive influence and two classes that indicate negative influence. Nevertheless, preparation applied by the lecturer in online learning should be more arranged. It is because the biggest influence comes from outside.